1994
DOI: 10.1093/jnci/86.6.446
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan (CPT-11) High-Dose Escalation Using Intensive High-Dose Loperamide to Control Diarrhea

Abstract: The effectiveness of CPT-11 might be increased by higher dose intensities, which can be made tolerable by control of diarrhea with loperamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(82 citation statements)
references
References 0 publications
2
77
0
3
Order By: Relevance
“…However, its use is limited by the severity of the diarrhea it causes, making an otherwise effective drug very difficult to use clinically. Oral loperamide works to slow diarrhea in many, 27 but there is still a significant incidence of grade 4 diarrhea and occasional mortality, leading to cessation of treatment. 4,5,28 Previous research has shown that palifermin is an effective antimucotoxic, reducing severity and duration of mucositis in both animal models 12,15,[20][21][22]29,30 and the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, its use is limited by the severity of the diarrhea it causes, making an otherwise effective drug very difficult to use clinically. Oral loperamide works to slow diarrhea in many, 27 but there is still a significant incidence of grade 4 diarrhea and occasional mortality, leading to cessation of treatment. 4,5,28 Previous research has shown that palifermin is an effective antimucotoxic, reducing severity and duration of mucositis in both animal models 12,15,[20][21][22]29,30 and the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhoea was another principal dose-limiting toxicity observed with this combination regimen (Table 4). The recent introduction of the use of high-dose loperamide by Abigerges et al (1994) has substantially reduced the previously marked CPT-11 -induced diarrhoea. However, 19% of patients still suffered from grade 3 or 4 delayed diarrhoea in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea occurring >12 hours after irinotecan was treated with loperamide 4 mg orally at the first episode followed by 2 mg every 2 hours (4 mg every 4 hours at night) until there was complete resolution of diarrhea for at least 12 hours. 27 Pretreatment and Follow-Up Studies. Patients had a complete history and physical examination, a determination of ECOG performance status, complete blood counts with differential, electrolytes, and standard liver and renal function tests performed within two weeks of treatment initiation and weekly while enrolled in the trial.…”
Section: Methodsmentioning
confidence: 99%